2019
DOI: 10.24042/ajpm.v10i2.4729
|View full text |Cite
|
Sign up to set email alerts
|

Probit Regression Analysis in Estimating the Effect of Learning Assisted by Cabri 3D on Students' Mathematical Understanding Ability

Abstract: Social connection requires each individual to have a strong understanding of the environment. Concept understanding can be improved through software. The goal of this research is to predict the effect of mathematics learning using Cabri 3D software. The dependent variable is the mathematics concept of understanding ability. The independent variable is the dummy variable that determines the type of the class. The value of the dummy variable for the class that applied the Problem-based Learning (PBL) assisted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…It indicates that the distribution of effect size data in the funnel plot was symmetrical (Nugraha & Suparman, 2021;Nurjanah et al, 2020). Moreover, six documents reported that the use of Cabri 3D had a strong positive effect on the students' mathematical academic outcome (Adirakasiwi & Warmi, 2018;Hendriana et al, 2019;Kariadinata et al, 2019;Marlena & Nugrheni, 2019;Saumi & Amalia, 2018;Widiastuti & Kurniasih, 2021). However, two documents reported that the use of Cabri 3D had a weak positive effect on the students' mathematical academic outcomes (Ma'sum et al, 2016;Natalliasari & Mulyani, 2017).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It indicates that the distribution of effect size data in the funnel plot was symmetrical (Nugraha & Suparman, 2021;Nurjanah et al, 2020). Moreover, six documents reported that the use of Cabri 3D had a strong positive effect on the students' mathematical academic outcome (Adirakasiwi & Warmi, 2018;Hendriana et al, 2019;Kariadinata et al, 2019;Marlena & Nugrheni, 2019;Saumi & Amalia, 2018;Widiastuti & Kurniasih, 2021). However, two documents reported that the use of Cabri 3D had a weak positive effect on the students' mathematical academic outcomes (Ma'sum et al, 2016;Natalliasari & Mulyani, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…The effectiveness of the Cabri 3D software for teaching geometry materials has been researched widely in Indonesia. Some studies revealed that Cabri 3D had a significant positive effect on the students' mathematical academic outcome (Adirakasiwi & Warmi, 2018;Hendriana et al, 2019;Kariadinata et al, 2019;Marlena & Nugrheni, 2019;Saumi & Amalia, 2018;Widiastuti & Kurniasih, 2021). Some studies, however, showed that Cabri 3D has an insignificant positive effect on the students' mathematical academic outcomes (Ma'sum et al, 2016;Natalliasari & Mulyani, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a good understanding of mathematical concepts, students will easily remember, use, and rearrange a concept that has been learned and can solve various variations of mathematical problems. This indicates that understanding the mathematical concepts is important to be instilled in students as early as possible so that they can solve problems better (Prahmana, 2013;Marlena & Nugrheni, 2019;Tamur & Kurnila, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…pemahaman konsep matematis (Kusmaryono, 2014;Minarni et al, 2016;NCTM, 2000) yang merupakan bagian penting dalam proses pembelajaran matematika (Lambertus, 2016). Pemahaman matematis penting untuk ditanamkan kepada siswa untuk dapat menyelesaikan permasalahan dengan lebih baik (Dewimarni, 2017;Marlena & Nugraheni, 2019;Prahmana, 2013). Jelas bahwa kemampuan pemahaman matematis berkontribusi pada kesuksesan siswa.…”
unclassified